Dietary intake of green tea polyphenols regulates insulin sensitivity with an increase in AMP‐activated protein kinase α content and changes in mitochondrial respiratory complexes. Issue 3 (23rd December 2012) - Serrano, José C. E.; Gonzalo‐Benito, Hugo; Jové, Mariona; Fourcade, Stéphane; Cassanyé, Anna; Boada, Jordi; Delgado, Marco A.; Espinel, Alberto E.; Pamplona, Reinald; Portero‐Otín, Manuel
<x xml:space="preserve">Abstract</x> Scope The intake of food rich in polyphenols is related to a lower incidence in almost all chronic degenerative diseases. However, relatively little is known about the molecular mechanisms involved in its antioxidant properties. The aim of this study was to determine whether the mechanism of action of polyphenols could be related to a modulation in energy uptake and metabolism, and further induced mitochondrial changes. Methods and results For this purpose, male C57BL6 mice were fed during 3 months with a tea‐based beverage rich in polyphenols. Insulin sensitivity, tissue oxidative damage biomarkers, as well as energy‐related signaling pathways were determined to evaluate its mechanism of action. As a result, a tissue‐ and protein‐specific subtle reduction in oxidative damage was observed. Skeletal muscle showed mitochondrial changes in respiratory complexes and an increase in AMP‐activated protein kinase α levels, suggesting reduced energy availability. These changes were also associated with adipose tissue cellular metabolism. This was confirmed by a decline in the potential of energy uptake, evidenced by a diminished intestinal and systemic absorption of carbohydrates together with an inhibition of insulin sensitivity. Conclusions Our results suggest that the mechanisms of action of green tea polyphenols may be related to their ability to modulate energy uptake leading to mitochondrial adaptations possibly responsible for the changes in protein oxidative damage.